FRI0377 Fc-Gamma Receptor Polymorphisms Differentially Influence Susceptibility to Systemic Lupus Erythematosus and Disease-Related Manifestations. (9th June 2015) - Tsang-A-Sjoe, M. W.-P.; Nagelkerke, S.Q.; Bultink, I.E.; Geissler, J.; Tanck, M.W.; Tacke, C.E.; Ellis, J.E.; Zenz, W.; Bijl, M.; Berden, J.H.; de Leeuw, K.; Derksen, R.H.; et al.
Abstract : Background: Genetic polymorphisms on the locus that encodes low-affinity Fc-gamma receptors (FcγRs) have been associated with systemic lupus erythematosus (SLE). Due to complexity of the locus, the individual contribution of a certain polymorphism to SLE remained largely unclear. Objectives: To determine relevant FcγR polymorphisms in relation to susceptibility to and disease-related manifestations of SLE. Secondly, to determine functional consequences of found genetic associations. Methods: Using multiplex ligation-dependent probe amplification, copy number regions (CNRs) and all known functional single nucleotide polymorphisms (SNPs) of FcγRII and FcγRIII were determined in a lupus nephritis-enriched cohort of 266 Dutch Caucasian SLE patients and 919 healthy Caucasian controls. Expression of FcγRs on leukocytes was assessed using flow-cytometry. Results: In multivariable analysis, low copy number of CNR1 including FCGR3B (OR 2.04, 95% CI 1.29 – 3.23, p=0.002 for 1 vs 2 copies), FCGR2A -131RR (OR 2.00, 95% CI 1.33 – 2.99, p=0.001 for HH vs RR), and the 2B.4 haplotype of FCGR2B (OR 1.59, 95% CI 1.13 – 2.24, p=0.008 for 2B.1/2B.4 vs 2B.4/2B.4) but not FCGR2C- ORF, were significantly and independently associated with susceptibility to SLE. The 2B.4 haplotype was negatively associated with lupus nephritis (OR 0.51, 95% CI 0.28 – 0.91). The 2B.4 haplotype led to surface expression of FcγRIIb on neutrophils and monocytes, but not to increased expression on B-cells, T-cells and NK cells (figure 1 ). Conclusions: In a comprehensive study, we show that a low gene copy number encoding FcgRIIIb, a decrease in FcgRIIa affinity, and expression of the inhibitory FcgRIIb on myeloid cells, independently contribute to SLE susceptibility. Interestingly, while the 2B.4 haplotype was associated with susceptibility to SLE, it was also negatively associated with lupus nephritis, one of the major SLE manifestations. Future studies are needed to confirm and further elucidate these findings. Disclosure of Interest: None declared